‘It is unbelievable’: Francis Kéré becomes first black architect to win the Pritzker prize - Wainwright, Oliver; @ollywainwright (The Guardian, 2022)
Burkinabe architect takes the profession’s highest honour, having made his name with schools and medical facilities in Africa, built by local communities with minimal resources
Keywords: Africa; Architecture; Art and design; Awards and prizes; Burkina Faso; Culture; World news; _z:class:countries